PERSONAL CHARACTERISTICS AND SOCIO-PSYCHOLOGICAL FACTORS AFFECTING IN THE PROCESS OF PROFESSIONAL SELECTION - Papoyan, V. R.; Karapetyan , M. A. (Modern Psychology, 2019)
In the article is presented those personal and socio-psychological factors that influence in the process of choosing a profession. From the psychological measurement point of view, the role of locus control, self-independence and initiative were observed in the choice of profession. Demand of the profession, subject preference, knowledge, ranking of the universities, advice of the adults and reputable people have been chosen as a socio-psychological factors. The experimental research was carried out with forty students with different profession in the graduation courses. The research was conducted by queries method, particularly the questionnaire of locus-control, selfindependence and initiative measurement were used, and the questionnaire designed by us to eliminate the influence of socio-psychological factors and the possible reasons for choosing a profession. As a result was found out that the above mentioned psychological characteristics have predetermined meaning in a such question, in which factors the future students choose their profession based on.
Keywords: professional preferences, personal characteristics, socio-psychological factors, locus control, self-independence, initiative